2020
DOI: 10.3390/app10228059
|View full text |Cite
|
Sign up to set email alerts
|

Credibility Based Imbalance Boosting Method for Software Defect Proneness Prediction

Abstract: Imbalanced data are a major factor for degrading the performance of software defect models. Software defect dataset is imbalanced in nature, i.e., the number of non-defect-prone modules is far more than that of defect-prone ones, which results in the bias of classifiers on the majority class samples. In this paper, we propose a novel credibility-based imbalance boosting (CIB) method in order to address the class-imbalance problem in software defect proneness prediction. The method measures the credibility of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Through the evaluation results, it was found that the proposed model surpassed several defect prediction models when applied to eight pairs of open-source Java projects. Tong et al [13] presented a novel approach to address the issue of class imbalance in SDP. The effectiveness of the proposed method was extensively evaluated on diverse datasets and compared with existing techniques.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the evaluation results, it was found that the proposed model surpassed several defect prediction models when applied to eight pairs of open-source Java projects. Tong et al [13] presented a novel approach to address the issue of class imbalance in SDP. The effectiveness of the proposed method was extensively evaluated on diverse datasets and compared with existing techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Upon examination of earlier research on SBP, it was observed that the majority of proposed techniques neglect the problem of class imbalance. Research that specifically dealt with the issue of class imbalance and provided solutions as referenced in [13], [15] emphasizes the crucial role of data balancing methods in enhancing SBP accuracy. Hence, the main aim of this study is to mitigate the problem of class imbalance and enhance the efficacy of the proposed models.…”
Section: Related Workmentioning
confidence: 99%
“…We manage this problem by modifying the original datasets to increase the realism of the data [36]. The most common methods used to deal with distributions of unbalanced classes are sampling techniques, might be divided into two categories: oversampling techniques and under-sampling techniques [43,44]. Oversampling techniques supplements instances of the minority class to the dataset, while the under-sampling techniques eliminate samples of the majority class for the goal of obtaining a balanced dataset [15].…”
Section: 4class Imbalance and Sampling Techniquesmentioning
confidence: 99%
“…Defect prediction 18 is an important research field of software engineering. Several approaches have been presented in the literature including ones that estimate the number of defects in a software program, 19 others 20 that find “associations” among defects (i.e., they detect additional problems starting from a defected piece of code), and ones 21 that classify the defect‐proneness of software components (as the ones discussed in this manuscript).…”
Section: Background and Related Workmentioning
confidence: 99%